A personal leadership statement (2022)
Leadership has been an over-defined term that has evolved along with human civilizations, even though there has not been one that seems to satisfy all perspectives. These last days have not escaped the discussion of what leadership should mean. On the other hand, if leadership is seen from the leader, the followers and the context perspective in which it is developed it gives us a new way of conceiving it. This paper will bring a renewed view of the leadership term, without leaving aside the author's point of view. In addition, we will see our assumptions, leadership empowerment and implications we as leader teachers must face in the future. If we in the servant leader's point of view put into practice the knowledge shared from now on, we will thrive whatever struggles we have.